Wave propagation in meshless numerical wave tank by using Hermite-type RPIM. (December 2020) - Gholamipoor, Morteza; Ghiasi, Mahmoud
Abstract: In this paper, the Hermite-type radial point interpolation method (RPIM) is proposed to develop the meshless numerical wave tank (NWT) for simulating the propagation of fully nonlinear water waves. The Hermite-type interpolation scheme, the radial basis functions (RBFs), and the polynomial functions are used to construct shape functions. These shape functions have better stability and can use any distribution nodes in the computational domain. The strong form of governing equation is transformed to a linear system of algebraic equations by the collocation approach. The material node approach is used to describe the fully nonlinear free surface boundary conditions, and the fourth-order Runge-Kutta (RK4) scheme is applied to update the free surface particles and the velocity potential. The numerical results are compared with other available solutions to confirm the accuracy and efficiency of the proposed numerical procedure. In addition, the accuracy and stability of Hermite-type RPIM compared with RPIM in this study. The numerical results demonstrate that good improvement in the accuracy of the numerical results is obtained after using the Hermite interpolation scheme.